48. AN UNUSUAL PRESENTATION OF ANGIOMATOID FIBROUS HISTIOCYTOMA (AFH). (February 2015) - Satgunaseelan, Laveniya; Wilsher, Mark; Maclean, Fiona; Bonar, Fiona
Abstract : AFH accounts for 0.3% of all soft tissue tumours and typically affects the extremities of children and young adults. Classically, microscopically, fascicles and sheets of oval to spindle cells, pseudovascular spaces, haemorrhage and a fibrous pseudocapsule rimmed by a lymphocytic infiltrate are noted. However, some cases lack these typical features, often bearing a striking resemblance to organising haematoma. Recently, cytogenetic analysis of AFH has shown specific translocations involving the EWSR1 and FUS genes. We document a seventy-one year old man who presented with a recurrent lesion of the left triceps muscle, six years after surgical excision. The radiology, morphology and immunohistochemical profile (EMA, desmin negative) of the initial lesion were those of an organising haematoma. (The lesion was completely embedded). It's true nature was only revealed at recurrence, where characteristic histological and immunohistochemical features of AFH were noted, prompting cytogenetic evaluation of both lesions. The EWSR1 rearrangement was present in the initial and recurrent lesion. Therefore, whilst morphological and immunohistochemical evidence of AFH were not present initially, recent cytogenetic advances have enabled confirmation of AFH at that time. This case illustrates the utility of cytogenetic testing in the diagnosis of AFH where the lesion deviates from the classical histological appearance. This possibility should be considered in haematomas in the absence of a specific cause at any age. References Bohman S, Goldblum JR, Rubin BP, et al . Angiomatoid fibrous histiocytoma: an expansion of the clinical and histological spectrum. Pathology 2014; 46: 199–204. Thway K. Angiomatoid fibrous histiocytoma: A review with recent genetic findings. Arch Pathol Lab Med 2008; 132: 273–7.